2011
DOI: 10.1136/emermed-2011-200133
|View full text |Cite
|
Sign up to set email alerts
|

A simple three-step dispatch rule may reduce lights and sirens responses to motor vehicle crashes

Abstract: A simple three-step dispatch rule for MVCs can safely reduce L&S responses by one-third, as judged by need for transport to a trauma centre or use of trauma centre resources. Prospective validation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…All of the studies that aimed to research how much time was saved by the use of L&S found that they do make a difference, although the time saved can vary to as little as 43 seconds. 10 Commercially developed dispatch systems can account for initial call type and priority, thus providing better guidance on when L&S response is most appropriate. Variability in time saved was seen across the published studies, and one possible cause of this is geographical differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies that aimed to research how much time was saved by the use of L&S found that they do make a difference, although the time saved can vary to as little as 43 seconds. 10 Commercially developed dispatch systems can account for initial call type and priority, thus providing better guidance on when L&S response is most appropriate. Variability in time saved was seen across the published studies, and one possible cause of this is geographical differences.…”
Section: Discussionmentioning
confidence: 99%
“…One factor is the effectiveness in reducing the ambulance response time (dispatch-to-scene-arrival interval) and the transport time (scene-departure-to-hospital-arrival interval). 10 Most of the current literature regarding L&S use focuses on EMS operational aspects such as the time saved by using them during response and/or transport. This is because prior to an ambulance arrival on scene, there is usually no health care professional there to care for the patient, and also limited information on the nature of said patient's injury/illness.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Priority 1 dispatch comprised 53% of all cases. On the one hand, this large allocation of Priority 1 dispatch relative to the number of time‐critical patients could be accepted as being consistent with the risk‐averse nature of ambulance dispatch systems, in erring towards higher priority dispatch unless good evidence supports lower priority dispatch . However, although accepting that some over‐triage is necessary because of uncertainties around patient condition (and how it might change), it is important to be mindful of the costs of high priority dispatch.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have shown the value of this approach within specific chief complaints, identifying potential improvements in discriminating patient acuity within the chief complaints of 'seizures', 4 'falls', 7 'breathing problems', 8 'chest pain', 1 'unknown problems' 9 and 'traffic accidents'. 10 However, few published studies have analysed variation in the accuracy of dispatch priority between chief complaints at a system-wide level. [11][12][13] In the present study, we take a system-wide approach to analysing the match between dispatch priority of ambulance calls and patient condition.…”
Section: Introductionmentioning
confidence: 99%
“…A large multicenter study published in 2010 examining 3656 trauma patients with unstable vital signs found no association between EMS activation, response, on-scene, transport or total time and patient mortality (17). In light of these considerations, several EMS agencies have instituted protocols designed to reduce the use of RLS (18–20). The majority, however, do not offer clearly articulated guidelines and depend solely on the discretion of the EMS provider.…”
Section: Introductionmentioning
confidence: 99%